Dual molecule targeting HDAC6 leads to intratumoral CD4+ cytotoxic lymphocytes recruitment through MHC-II upregulation on lung cancer cells - Harry Sokol; Chloé Michaudel; Sarah Ducellier; Mélanie Demeules; Boris Letribot; Massimiliano Gaetani; Abdallah Hamze; Mouad Alami; Mégane Nascimento; Sébastien Apcher (Journal for ImmunoTherapy of Cancer)
Background Despite the current therapeutic treatments including surgery, chemotherapy, radiotherapy and more recently immunotherapy, the mortality rate of lung cancer stays high. Regarding lung cancer, epigenetic modifications altering cell cycle, angiogenesis and programmed cancer cell death are therapeutic targets to combine with immunotherapy to improve treatment success. In a recent study, we uncovered that a molecule called QAPHA ((E)−3-(5-((2-cyanoquinolin-4-yl)(methyl)amino)−2-methoxyphenyl)-N-hydroxyacrylamide) has a dual function as both a tubulin polymerization and HDAC inhibitors. Here, we investigate the impact of this novel dual inhibitor on the immune response to lung cancer.Methods To elucidate the mechanism of action of QAPHA, we conducted a chemical proteomics analysis. Using an in vivo mouse model of lung cancer (TC-1 tumor cells), we assessed the effects of QAPHA on tumor regression. Tumor infiltrating immune cells were characterized by flow cytometry.Results In this study, we first showed that QAPHA effectively inhibited histone deacetylase 6, leading to upregulation of HSP90, cytochrome C and caspases, as revealed by proteomic analysis. We confirmed that QAPHA induces immunogenic cell death (ICD) by expressing calreticulin at cell surface in vitro and demonstrated its efficacy as a vaccine in vivo. Remarkably, even at a low concentration (0.5 mg/kg), QAPHA achieved complete tumor regression in approximately 60% of mice treated intratumorally, establishing a long-lasting anticancer immune response. Additionally, QAPHA treatment promoted the infiltration of M1-polarized macrophages in treated mice, indicating the induction of a pro-inflammatory environment within the tumor. Very interestingly, our findings also revealed that QAPHA upregulated major histocompatibility complex class II (MHC-II) expression on TC-1 tumor cells both in vitro and in vivo, facilitating the recruitment of cytotoxic CD4+T cells (CD4+CTL) expressing CD4+, NKG2D+, CRTAM+, and Perforin+. Finally, we showed that tumor regression strongly correlates to MHC-II expression level on tumor cell and CD4+ CTL infiltrate.Conclusion Collectively, our findings shed light on the discovery of a new multitarget inhibitor able to induce ICD and MHC-II upregulation in TC-1 tumor cell. These two processes participate in enhancing a specific CD4+ cytotoxic T cell-mediated antitumor response in vivo in our model of lung cancer. This breakthrough suggests the potential of QAPHA as a promising agent for cancer treatment.